Improving the torsion performance of IPMC by changing the electrode separation - Bing Xu (Nature Portfolio, 2021)
Abstract Ionic polymer metal composites (IPMCs) are widely studied as actuators and sensors, due to their large bending motion, flexibility and being light-weight. Nowadays, IPMCs are used in the bionic field, for example, to achieve bending and twisting movements of wings and fins. In this paper, a method is proposed to optimize the torsion performance of IPMCs by changing the electrode separation. The IPMCs with patterned electrode fabricated by masking technique are proposed to accomplish twisting motion. The result indicates that the torsion performance is improved as the electrode separation increased. Thereby it provides a new strategy for the bionic field with twisting behavior.